2021
DOI: 10.1186/s12933-021-01321-7
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose index combined with plaque characteristics as a novel biomarker for cardiovascular outcomes after percutaneous coronary intervention in ST-elevated myocardial infarction patients: an intravascular optical coherence tomography study

Abstract: Background and aim This prospective study explored plaque morphology according to the underlying culprit lesion pathology (rupture versus erosion) in relation to the triglyceride glucose (TyG) index in patients with acute ST-elevated myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention and optical coherence tomography (OCT) for culprit lesions to elucidate the effects of the TyG index and type of plaque on the incidence of major adverse cardiovascular events (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…In fact, among the four studies they included, two found a statistically significant association between the TyG index and all-cause mortality [ 30 , 31 ], while the other two did not [ 28 , 32 ]. In studies of different populations, most articles found a positive association between the TyG index and cardiovascular mortality/all-cause mortality [ 14 , 33 , 34 ]. Another recent study of the Kangbuk Samsung Health Study cohort [ 35 ], including 255,508 relatively healthy populations, supported that the TyG index is associated with an elevated risk of all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, among the four studies they included, two found a statistically significant association between the TyG index and all-cause mortality [ 30 , 31 ], while the other two did not [ 28 , 32 ]. In studies of different populations, most articles found a positive association between the TyG index and cardiovascular mortality/all-cause mortality [ 14 , 33 , 34 ]. Another recent study of the Kangbuk Samsung Health Study cohort [ 35 ], including 255,508 relatively healthy populations, supported that the TyG index is associated with an elevated risk of all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the triglyceride-glucose (TyG) index, measured by the fasting plasma glucose and triglyceride, has been proposed as a reliable surrogate marker of IR and shown to highly correlate with IR [5,6]. Growing evidence has been demonstrated that the TyG index is related to adverse cardiovascular outcomes in the general population [7][8][9], as well as among certain high-risk patients, such as diabetes [10], hypertension [11], myocardial infarction [12], acute coronary syndrome [13], and after percutaneous coronary intervention [14]. In addition, several studies also report a predictive role of the TyG index with adverse cardiovascular outcomes among the general population [7,15] and patients with cardiovascular diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, carotid plaque burden was used as a marker of atherosclerosis, which manifested as the change in the plaque score obtained from different carotid districts. As reported in the literature, the prevalence of carotid artery plaque shows a good correlation with the presence of atherosclerosis and can well reflect the overall severity of atherosclerosis in the vasculature ( 25 , 26 ). The association between the TyG index and arteriosclerosis has been demonstrated in some previous studies.…”
Section: Discussionmentioning
confidence: 62%
“…Research has also shown that the TyG index, as a surrogate for IR, is a marker of the presence of non-calcified or mixed plaques in coronary arteries in asymptomatic individuals (28). Other studies support that a higher TyG index value is associated with the severity of coronary artery stenosis in not only patients with acute ST-elevated myocardial infarction but also asymptomatic patients with T2D (26,29). However, their focus of these studies falls outside the areas of carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that a low ratio of eicosapentaenoic acid to arachidonic acid was associated with higher vulnerability of coronary plaques to rupture [ 40 ]. The triglyceride glucose index combined with the morphological characteristics of plaque could be used to predict adverse events in patients with STEMI [ 41 ]. The combination of different biomarkers, such as soluble lectin-like oxidized LDL receptor-1, MMP-9, WBC count, and peak creatine kinase-MB, could also be used to identify plaque rupture compared with other individual biomarkers in patients with ACS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%